Strategi Komunikasi Digital Oleh Agensi K-Pop (Analisis Pengelolaan Konten Dan Interaksi Penggemar Melalui Akun Instagram Treasure Dan Enhypen) - Siti Maesyaroh,, Syarah; Yuniar Naqiah, Listia (Jurnal Syntax Fusion, 2024)
Instagram has become a strategic communication platform in the K-pop industry to build an emotional connection between idols and fans. This study analyzes the digital communication strategies implemented by YG Entertainment and BELIFT LAB in managing Treasure and Enhypen's Instagram accounts, as well as their impact on idol image and fan loyalty. Using a qualitative approach with a comparative case study design, this study observed the content and interactions in both accounts during the period October 2024 to January 2025. Data collection techniques include digital content analysis and passive participatory observation of Instagram's posts, comments, live sessions, and interactive features. The results showed that YG Entertainment applied a mystery marketing strategy with a selective approach that created an aspirational image and exclusivity value, while BELIFT LAB used a transparency strategy with frequent interactions that built perceived intimacy and friendship-based parasocial relationships. Both strategies are effective in converting online engagement into offline support in the form of album purchases and concert tickets, as well as forming a solid fan community. However, there are challenges in creating balanced two-way communication, managing diverse global fandom, and long-term sustainability. This research contributes to the understanding of the dynamics of digital communication in the contemporary entertainment industry.